Wkład Karola Marksa do teorii cyklu koniunkturalnego - Barczyk, Ryszard; Kowalczyk, Zygmunt (Wydział Prawa i Administracji UAM, 1984)
A reconstruction of Marxian hypotheses and thoughts pertaining to theoretical interpretation of crisis phenomena and cyclical fluctuations in capitalist economy is a main research task of this study. The following were analysed for that purpose: potentials of a crisis of overproduction, actual reasons of crises resulting from the basic contradictions of capitalist mode of production, and a sequence of forming business cycle phases as a result of contradictory developement of capitalist economy. The main thesis of Marx that a capitalist economy suffers from overproduction crises and a cyclicality of a capitalist reproduction is an effect of the law of crises became a milestone in the 19 c. history of economic thought. The Marxian analysis of crisis phenomena and mechanism of business cycle is carried out on a high level of abstraction, it can be therefore stated that Marx was a creator of general hypotheses on these processes only. Reflections of K. Marx on reasons of the overproduction crisis and the cyclical fluctuations can be classified as the endogenous concept. The main reason of periodical crises of overproduction lies, according to Marx, in the essence of capitalist mode of production. Changes in the investment process are the key to explain a mechanism of business cycle »as it stated by Marx in his concept overproduction crises and business cycle. Yet, the work of K. Marx in the scope of business cycles in capitalist economy can not be considered as a complete and systematic theory of business cycle. On creating his concept of business cycle, Marx paid a particular attention to crisis phase maintaining that it is the essential phase for the whole cycle. A little attention was only paid to periods of revival and prosperity. Marx did not study morphological features of the cycle. Nor proposed he any qualitative or quantitative criteria or 'methods to separate and analyse respective phases of the business cycle.
Contribution of Karl Marx to the theory of business cycles